Translation and validation of the medication management patient satisfaction survey: The Lebanese Arabic version - Alaa Eddine, Nada; Schreiber, James B.; Amin, Mohamed Ezzat Khamis (Frontiers in Pharmacology, 2023)
Background: No Arabic translation exists for the Medication Management Patient Satisfaction Survey (MMPSS), a 10-item psychometrically valid patient satisfaction survey tool developed to assess patient satisfaction for Comprehensive Medication Management (CMM). The objective of this study is to translate MMPSS into Lebanese Arabic while culturally adapting and assessing the psychometric properties of translated MMPSS in the outpatient setting. Methods: Guidelines for translation, adaptation, and validation of instruments for cross-cultural healthcare research were followed. The process included forward translation, expert panel review, back-translation, pretesting, and cognitive interviewing. Participants were approached after picking up their medications from the pharmacy at a primary care facility. The MMPSS was administered verbally by two trained data collectors. Instrument psychometric analyses included testing both for reliability using Cronbach’s alpha (α) and McDonald’s omega (ꞷ) and for construct validity using Exploratory Factor Analysis (EPA). Pearson correlations between items were calculated. Results: During the translation process, the term “clinical pharmacist” was changed to “pharmacist today” for improved understanding. Four items were adapted through minor linguistic modifications. Data were collected from 143 patients. The mean age of participants was 72 years. Participants were mostly females (69%) and had an average of 4 comorbidities and 8 daily medications. Findings from Cronbach’s α and McDonald’s ꞷ indicated that the internal consistency among items from one to nine was very strong (α=0.90; ꞷ=0.90). EPA indicated that all items are strongly influenced by one factor, except for item six, “My clinical pharmacist is working as a team member with my other healthcare providers” which was the least influenced (loading=0.44) with the highest uniqueness (0.81). The latent factor captured over 50 % of the variance originally observed between variables. Items four and five “My clinical pharmacist helped me find easier ways to take my medicines” and “My clinical pharmacist helped me understand the best ways to take my medicines”, had the strongest correlation (0.77), while the weakest correlation was seen between item six and other items. Conclusion: The Lebanese Arabic version of the MMPSS was produced as a brief tool to serve as a valid and reliable instrument for measuring patient satisfaction with CMM.